Numerical investigation of the plasma-aided fabrication of stoichiometric InAs nanodots at early stage of the growth - Alizadeh, M.; Mehdipour, H.; Goh, B.T.; Rahman, S.A. (American Institute of Physics, 2013)
Using numerical modeling of the plasma sheath and key surface processes, the plasma-aided fabrication of InAs nanodots is investigated at early stage of the growth. Roles of different plasma process parameters, such as electron temperature, electron number density, and ion-to-electron density ratio, in achieving the stoichiometric growth of the nanodots are explored and conditions to achieve a highly stoichiometric InAs composition are discussed. It is shown that the nanodots get larger with increasing the electron temperature and electron number density, whereas they shrink in size with increasing the ion-to-electron density ratio. Moreover, it is shown that with increase in the electron temperature and electron number density stoichiometric saturation state can be reached shortly, which this enables the fabrication of highly stoichiometric array of nanodots within shorter processing time. The results obtained can open a path toward nucleation and growth of an array of nanodots with desired structural composition and size distribution.